Adaptive Readiness of Pre-Service Teachers: A Study of PLP Students’ Responses to Real-World School Dynamics - Heri Alfian; Muhammad Irfan Rahim (Universitas Islam Negeri Palopo, 2026)
Empirical research on pre-service teachers' adaptive readiness during practicum is still fragmented and dominated by qualitative accounts that are rarely operationalized into a measurable, multidimensional construct, especially in the Indonesian context, despite increased scholarly attention to teacher competence. Because it determines how well aspiring teachers convert university-based theory into successful, context-responsive practice under actual classroom uncertainty, adaptive readiness has emerged as a crucial concept in modern teacher education. A crucial transitional stage that often highlights a disconnect between academic theory and erratic classroom dynamics is the Classroom-Based Teaching Practicum (PLP). In order to successfully negotiate classroom management, learner variety, and institutional cultures, pre-service teachers must possess adaptive preparedness. The objectives of this study are to assess PLP students' levels of adaptive preparedness, pinpoint the key variables influencing their ability to adjust, and examine how they react to real-world academic difficulties. 87 pre-service teachers who finished their practicum assignments participated in a descriptive-quantitative study using an explanatory methodology. A validated five-dimensional questionnaire was used to gather the data, which were then examined using multiple linear regression and descriptive statistics. Overall, the results show a high degree of adaptive readiness. The best indicators were found to be behavioral and social interaction adaptability, which together accounted for 53% of the variation in overall readiness (M = 3.82, SD = 0.47). The best predictors were behavioral adaptability (β = .39, p < .001) and social interaction adaptability (β = .31, p = .002), with the full five-predictor regression model accounting for 53% of the variance in overall readiness, R² = .53, F (5, 81) = 19.24, p < .001. On the other hand, the most vulnerable dimension was found to be emotional readiness, which had the most variability and the lowest mean score, especially when it came to controlling student discipline and frustration. The findings show that the development of adaptive preparedness varies by dimension. This study provides a fresh empirical approach that has not yet been created in national teacher education research by operationalizing adaptive readiness into a validated, multidimensional instrument within the Indonesian PLP environment. To create resilient teachers ready for today's pedagogical challenges, teacher education programs must methodically incorporate autonomous scaffolding and emotional resilience training into practicum curricula. In addition to providing a theoretical contribution, a multidimensional model of adaptive preparedness that has been validated, these findings also provide practical goals for practicum curriculum improvement.